Classification of Chemicals According to UN-GHS and EU-CLP: A Review of Physical Hazard Classes and Their Intricate Interfaces to Transport and Former EU Legislation - Wilrich, Cordula; Brandes, Elisabeth; Michael-Schulz, Heike; Schröder, Volkmar; Schwarz, Silke (Open Science Journal, 2018)
The Globally Harmonized System of Classification and Labelling of Chemicals (UN-GHS) is being implemented in more and more countries all over the world; the EU has done so with the CLP-Regulation (EU-CLP). Compared to the undeniably important questions on health and environmental hazards, the classification of physical hazards of chemicals often has not been in the focus, although their implementation can be challenging and there are traps and pitfalls to be avoided. The following overview of the classification systematics for physical hazards aims at a principle understanding without detailing all criteria or test methods. Similarities and differences between the classification systems of the UN-GHS and EU-CLP, the transport of dangerous goods and the former EU system are reviewed with regard to the physical hazard classes. Available physical hazard classifications for the transport of dangerous goods and according to the former EU system can be used as available information when classifying according to the GHS. However, the interfaces of these classification systems and their limitations have to be understood well when concluding on GHS/CLP classifications. This applies not only to industry when applying CLP but especially to legislators when adapting legislation that in one way or another refers to the classification of chemicals.